Evaluation of mass transfer effect and response surface optimization for abatement of phenol and cyanide using immobilized carbon alginate beads in a fixed bio‐column reactor. Issue 2 (21st January 2020) - Pathak, Uttarini; Banerjee, Avishek; Roy, Teetas; Das, Subham Kumar; Das, Papita; Kumar, Tarkeshwar; Mandal, Tamal
Abstract: Coke oven sectors dispense phenol and cyanide into the circumferential ecosystem, which becomes a serious concern to the subsistence of the flora and fauna. The current study investigates phenol–cyanide treatment using carbon alginate beads immobilized with mixed bacterial consortium. Response surface using central composite design was contrived for the batch and packed bed bio‐column optimization study. The optimal removal conditions obtained in batch study were 89.77% and 82.33% for phenol and cyanide, respectively, with 10‐g/L adsorbent dosage, time 2 hr, and particle diameter 0.3 cm, whereas 87.22% and 90.97% with 22‐cm column height, column diameter 3 cm, 10‐ml/min flow rate, and 1‐hr operation time. The actual exposure time of the pollutants in the bio‐column reactor was calculated to be 22.15 min. Analysis of variance and model statistics predicted a high coefficient of determination for column operation with R 2 = .9950 (phenol), R 2 = .9976 (cyanide), and p values < .0001 stating significant model. The quantitative estimation of the combined external mass transfer and biodegradation effect was performed to evaluate correlation as (phenol) and (cyanide) with k m = 0.052 and k m = 0.055 cm/hr, respectively. The surface morphological study was executed by field emission scanning electron microscopy and Brunauer–Emmett–Teller surface area analysis depicting bacterial film development on the porous carbon matrix for effective treatment of binary system.